Peace and Order Programs of the Barangay Officers at Barangay Sta Lucia in Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The BPSO and police law enforcers have implemented guidelines to ensure the safety andsecurity of individuals in the community. Peace and order is one of the major concernsaddressed in each agency.In the overall evaluation of the respondents in terms of patrol schedules, CCTV cameras, andgates per area, Lucia, Quezon City, rated good. The majority of the respondents said thatteaching the locals how to keep the barangay peaceful and orderly was the most importantstep. The residents would be able to take an active role in initiatives to preserve peace andorder in the barangay. Hence, the researchers advise that teaching them is important.Additionally, it will be able to give the locals the tools they need to become good citizens. It isalso advised that a meeting of the barangay staff and citizens be held to explore ways toenhance the execution of peace and order in the barrio. Doing this will also solve the issuesthat the locals have with the CCTV cameras that have been placed, the need for morecameras, and the locals' worry about the neighborhood gates.
Keywords: Criminology